2004
DOI: 10.1136/jcp.2003.011445
|View full text |Cite
|
Sign up to set email alerts
|

The practical application of reflectance spectrophotometry for the demonstration of haemoglobin and its degradation in bruises

Abstract: Aims: To develop a non-invasive method to demonstrate the presence of haemoglobin and its degradation products in bruises in live human subjects for the purposes of objectively assisting in the determination of the age of a bruise. Methods: The cuvette holder unit of a Cary 100 Bio UV-Visible Spectrophotometer was replaced with the manufacture's fibre optic cable and optical reflectance probe. The probe was placed on the skin surface. The absorption spectrum from 780 to 380 nm was collected and transformed int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 30 publications
4
74
0
Order By: Relevance
“…The visual appearance of a bruise will be dependent on the time after impact, and optical methods can be used to monitor and characterize the observed changes. Reflection spectroscopy has been applied to characterize bruises with good results [12][13][14][15]. Bohnert et al [12] published a relation between reflectance spectra, observed bruise color and depth of injury in post mortem cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The visual appearance of a bruise will be dependent on the time after impact, and optical methods can be used to monitor and characterize the observed changes. Reflection spectroscopy has been applied to characterize bruises with good results [12][13][14][15]. Bohnert et al [12] published a relation between reflectance spectra, observed bruise color and depth of injury in post mortem cases.…”
Section: Introductionmentioning
confidence: 99%
“…They found that superficial hemorrhages cause bright red bruises, while deep subcutaneous bruises appear blue or purple. Hughes et al [13] used reflectance spectroscopy to quantify bilirubin in bruises of various age, and Randeberg et al [14] identified hemoglobin content in the skin, hemoglobin oxygenation, and bilirubin content as potential indicators of bruise age. Randeberg et al [15] later published a mathematical model to predict the age of a bruise from a reflectance measurement.…”
Section: Introductionmentioning
confidence: 99%
“…This change in bruise colour is due to the inflammatory Strappini, Metz, Gallo and Kemp process, whereby macrophages are recruited to the injured area and ingest red blood cells and metabolize the haemoglobin first to biliverdin and then rapidly to bilirubin (Hughes et al, 2004). Based on empirical observations, Grandin (2000) concluded that in beef cattle carcasses it would be possible to separate bruises into at least two categories: fresh bruises and bruises that are several days or weeks old.…”
Section: Estimating Bruise Agementioning
confidence: 99%
“…The latter accounts for the numerous studies carried out in recent decades with the aim of developing a method for ageing bruises in human skin (Langlois and Gresham, 1991;Betz, 1994;Sawaguchi et al, 2000;Bariciak et al, 2003;Bonelli et al, 2003;Hughes et al, 2004 andRandeberg et al, 2006;Grellner and Madea, 2007;Kondo, 2007).…”
Section: Forensic Investigation Of Human Skin Bruisesmentioning
confidence: 99%
“…Depending on its wavelength, light can penetrate the skin and has the potential to detect bruises, which are primarily located below the level of the epidermis (>15μm) within the vascular dermis (Hughes, Ellis, Burt, & Langlois, 2004;Langlois & Gresham, 1991;Sandby-Moller, Poulsen, & Wulf, 2003;Wright & Golden, 2010). At this point, light most commonly interacts with the tissues in three ways: reflection, absorption or fluorescence (Marin & Buszka, 2013).…”
Section: Introductionmentioning
confidence: 99%